Respostas
respondido por:
1
P(0) significa que você deve substituir o "x" por 0, então ficaria:
P(0)=3.(0-5)(0+6)
P(0)=3.(-5)(6)
P(0)=(-15)(6)
P(0)=-90
Espero ter ajudado!
P(0)=3.(0-5)(0+6)
P(0)=3.(-5)(6)
P(0)=(-15)(6)
P(0)=-90
Espero ter ajudado!
FláviaFernandes7899:
ajudou sim!! Obrigada ❤
respondido por:
1
P(0) = 3.(x-5) . (x+6) (SÓ SUBSTITUIR X PELO 0)
P(0) = 3.(0-5) . (0+6)
P(0) = 0 - 15 . 6
P(0) = -90
P(0) = 3.(0-5) . (0+6)
P(0) = 0 - 15 . 6
P(0) = -90
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás